Adipose-derived mesenchymal stem cells and their derivatives in inflammatory skin diseases: a systematic review - Matwiejuk, Mateusz; Mikłosz, Agnieszka; Myśliwiec, Hanna; Chabowski, Adrian; Flisiak, Iwona (Frontiers in Immunology, 2025)
Adipose-derived mesenchymal stem cells (ADMSCs) offer a multifaceted approach to treating immune-mediated skin diseases by modulating the immune system and promoting tissue regeneration. Specifically, their ability to differentiate into multiple cell types such as keratinocytes and fibroblasts, modulate immune responses, and release growth factors and cytokines underscores their potential in treating a wide range of immune-related skin conditions. ADMSCs significantly reduced various aspects of psoriasis, including scaling, thickness, and erythema. Moreover, cell-free therapy has even better therapeutic potential. It has been shown that ADMSC-derived exosomes can effectively alleviate pathological symptoms of atopic dermatitis, including clinical score, serum IgE levels, eosinophil amount, and infiltration of immune cells in skin lesions. This systematic review summarizes the most relevant preclinical and clinical studies on the therapeutic use of ADMSCs and their small extracellular vesicles in the treatment of common skin diseases like psoriasis, atopic dermatitis, localized scleroderma and acne vulgaris.